The Spirit and the Marketplace: How Chaplaincy is Evaluated in Contemporary Health Care Research - Thomas M. Kelly (Journal of Religion & Society Supplement Series, 2026)
Professional chaplaincy is a specialized ministry that provides spiritual, religious, pastoral, ethical, and/or existential care in secular settings, such as hospitals, prisons, or the military, by individuals ordained or endorsed by their faith communities (including humanist societies and other secular bodies). The essence of chaplaincy is a relational encounter characterized by openness and engagement that begins with the needs of the patient, client, or recipient of such ministry. The art of this encounter is as varied as the people practicing it, but the efficacy of chaplaincy in healthcare settings is well established. This article explores the tension between a positivist outcome-based evaluation of chaplaincy and the relationship presence-based experience of the ministry. It concludes with a modest way forward which distinguishes between different forms of evaluation relative to specific audiences.